Determinants of Rabies Post-exposure Prophylaxis Drop-Out in the Region of San-Pedro, Côte d'Ivoire - N'Guessan, Rose Delima; Heitz-Tokpa, Kathrin; Amalaman, Djedou Martin; Tetchi, Sopi Mathilde; Kallo, Vessaly; Ndjoug Ndour, Andrée Prisca; Nicodem, Govella; Koné, Issiaka; Kreppel, Katharina; Bonfoh, Bassirou (Frontiers in Veterinary Science, 2022)
Despite deaths from rabies, being 100% preventable with post-exposure prophylaxis (PEP), canine rabies causes about 59,000 human deaths worldwide annually, of which about half is occurring in Africa. In Côte d'Ivoire, rabies remains a threat partly due to the drop-out of the life-saving human PEP treatment among people exposed to dog bites. Each year, half of the victims beginning the treatment, do not complete the remaining doses. The current study therefore assesses the determinants of the drop-out of the life-saving treatment among people exposed to rabies in the department of San-Pedro in Côte d’Ivoire. Methods: A mixed-methods approach with questionnaires, observation, individual interviews and focus group discussions was used to gather socio-demographic and economic data from 235 participants about possible reasons for abandoning the treatment. from 235 selected people. The study population consisted of patients and medical and veterinary health professionals who were selected using stratified sampling and purposive selection from a database available at the Rabies Center. Result: The drop-out of PEP treatment was related to perception bias and the low attendance of health care and vaccination centers in the population's habits. Quantitative analysis also shows differences between rural and urban areas and association with age when it comes to treatment completion. The dropout rate was most significant among patients who in case of other illness did not routinely see a doctor or go to vaccination centers. The rate was also higher among those who believed that dog-related injuries could be easily treated at home and who believed that a person with rabies could be cured without completing the preventive treatment. Also, insufficient provision of health information on rabies and logistic constraints related to the practical organization of treatment including the long distance to the anti-rabies center and weaknesses in the patient follow-up procedure did not contribute to the completion of PEP. Conclusion: Established determinants for drop-out provide a framework for effective design and implementation of rabies control strategies to accelerate rabies deaths elimination efforts. In particular, access to PEP and community knowledge about rabies need to be improved and integrated in the health system and education system respectively.